Peningkatan Pemahaman terhadap Fintech Lending Pada Kelompok Dasa Wisma RT 03 RW 10 Perumnas Patrang : - - Mufidah, Ana; Puspitasari, Novi; Perwitasari W, Dwi; Rijal, Salahuddin (Jurnal Pengabdian Masyarakat Akademisi, 2025)
In response to the economic downturn caused by the COVID-19 pandemic, collaboration among regulators, ministries, and relevant institutions is essential to ensure broader access to financial services. One promising solution is fintech lending, which offers faster, easier access to capital without requiring substantial collateral, unlike traditional banks. Fintech holds significant potential to support economic recovery efforts. However, alongside these benefits, fintech lending also presents various challenges—particularly related to illegal lending services. Common issues include threats from service providers, a lack of transparency regarding interest rates and service fees, and penalties for late payments. There are also unethical practices such as the unauthorized sharing of borrowers’ contact information. Therefore, public education and awareness are crucial to help people make informed choices when using fintech lending services. Understanding the difference between legal and illegal fintech platforms is key to avoiding potential risks and financial harm.